Cluster approach in the pedagogical research of future teachers (The Peerian Journal, 2022)
The modern cluster system in education is aimed at the development of the individual and its maturity, and its interconnectedness is a chain of lifelong learning, which includes such processes as kindergarten, school, lyceum, college, university, doctorate, training.